Prenatal Diagnosis of Beta-Thalassemia Disease and Fate of Fetuses Among Beta-Thalassemia Carrier Mothers: An Experience at Tertiary Care Hospital of Rahim Yar Khan (Medical Forum Monthly, 2023)
Objective: To assess the status of beta thalassemia disease in fetuses of beta thalassemia carrier mothers and to determine the fate of these fetuses.Study Design: A cross sectional studyPlace and Duration of Study: This study was conducted at the Pathology and Gynecology & Obstetrics Departments of Sheikh Zayed Medical College/Hospital, Rahim Yar Khan from July 2022 to June 2023.Materials and Methods: Ninety pregnant women with known thalassemia carrier status participated in the current study. Beta-thalassemia carrier status was confirmed at Pathology Department while antenatal examination and assessment was performed at Department of Gynecology & Obstetrics. After getting the DNA and PCR done, the fate of fetuses was recorded on follow up of the study subjects. The collected data was analyzed using version 25.Results: Of the 90 women who had CVS, 21 (23%) had fetuses with the thalassemia major gene, 34 (37%) had fetuses with the thalassemia minor gene, and 26 (28%) had fetuses that were otherwise healthy and normal. Nine (10%) women experienced miscarriages either before or after the test. Thirteen (62%) of the 21 patients with fetuses of thalassemia major gene underwent pregnancy termination.Conclusion: The results of the current study showed that a significant number of mothers carry fetuses with thalassemia major gene which strongly imply that prenatal diagnosis of thalassemia major and CVS aid in prompt decision-making regarding pregnancy termination in thalassemia major, hence reducing the disease burden.